Inequality and relative reliance on tariffs : theory and evidence - Margarita Katsimi; Thomas Moutos (Center for Economic Studies and ifo Institute (CESifo), 2005)
In this paper we construct a Ricardian model of trade in vertically-differentiated products between a developing country and the (developed) rest of the world. Despite labour being the only factor of production in this model, tariffs (in addition to income taxes) have distributional consequences because the high-quality imported varieties are consumed only by high-income households. The model predicts a U-shaped relationship between income inequality and the median-voter's preferred reliance on tariffs versus income taxes in order to effect the desired redistribution. Using data from 44 countries we test for the existence of this U-shaped relationship by estimating a cross-sectional regression relating the ratio of the tariff rate over the tax rate to inequality and a set of control variables such as GDP per capita, openness, the degree of democracy and area dummies. We find that the model's predictions are supported by the data.
Keywords: H23; F13; 330; inequality; tariffs; median-voter; trade; vertical differentiation; Zollpolitik; Einkommensverteilung; Einkommensteuer; Komparativer Kostenvorteil; Median Voter; Schätzung; Theorie; Welt